2013
DOI: 10.1002/dneu.22119
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cell apoptosis after low‐methylmercury exposures in postnatal hippocampus produce persistent cell loss and adolescent memory deficits

Abstract: The developing brain is particularly sensitive to exposures to environmental contaminants. In contrast to the adult, the developing brain contains large numbers of dividing neuronal precursors, suggesting that they may be vulnerable targets. The postnatal day 7 (P7) rat hippocampus has populations of both mature neurons in the CA1-3 region as well as neural stem cells (NSC) in the dentate gyrus (DG) hilus, that actively produce new neurons that migrate to the granule cell layer (GCL). Using this well-character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 45 publications
5
59
0
Order By: Relevance
“…Similar results have been reported in animal models of brain development after exposure to MeHg in utero [8,9]. Moreover, extensive evidence has demonstrated that MeHg can lead to neural cell death, as well as to cytoarchitectural alterations in the nervous system [10,11,12,13,14]. There is an abundance of knowledge regarding reactive oxygen species (ROS) and especially effects of low-level MeHg exposure on cell cycle regulators in neural stem cells in vitro and in vivo [15,16,17].…”
Section: Introductionsupporting
confidence: 74%
“…Similar results have been reported in animal models of brain development after exposure to MeHg in utero [8,9]. Moreover, extensive evidence has demonstrated that MeHg can lead to neural cell death, as well as to cytoarchitectural alterations in the nervous system [10,11,12,13,14]. There is an abundance of knowledge regarding reactive oxygen species (ROS) and especially effects of low-level MeHg exposure on cell cycle regulators in neural stem cells in vitro and in vivo [15,16,17].…”
Section: Introductionsupporting
confidence: 74%
“…Likewise, microarray analysis of adult zebrafish brain tissue after intraperitoneal injection of MeHg found significant alteration of gene pathways regulating cell survival and apoptosis in favor of cell death (Richter et al 2011). And a decreased neural proliferation and increased cell death in the hippocampus of rats exposed perinatally to MeHg lead to impairment in memory function lasting through adolescence (Falluel-Morel et al 2007; Sokolowski et al 2013). In our stage 12 embryos, microarray results displayed a strong upregulation of mitochondrial associated apoptotic genes such as cytochrome c (p < 0.005) and caspase 9 (p < 0.03), but found a downregulation of bax (p < 0.012) and no significant change in caspase 8 (p > 0.08), caspase 3 (p > 0.07), or p53 (p > 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…Rats exposed to a single injection of 5μg/g MeHg at P7 showed profound juvenile spatial learning impairment and decreases in cell number in P21 hippocampus, that correlated with acute caspase-dependent apoptosis [27]. Furthermore, acute exposure to an environmentally relevant dose of MeHg (0.6μg/g, 24h) in P7 rats, induced caspase-3 activation in neural stem cells (NSCs) of the dentate gyrus (DG), and caused hippocampal-dependent memory deficits during adolescence, assessed by Morris water maze [123]. In addition, a significant degeneration of neuritic processes, and either apoptotic or necrotic death was observed in cortical cultures obtained from pups born to 8 mg/kg MeHg-exposed dams, which was correlated with long term memory impairment of adult offspring subjected to a memory task [73].…”
Section: Mechanisms Of Mehg-induced Developmental Neurotoxicitymentioning
confidence: 99%